CORE SUB-COOLED BOILING OF THE BANDUNG TRIGA 2000 REACTOR - K Kamajaya; Henky P.R; E Umar; P. Ilham Yazid (Mesin, 2008)
In 2000, the TRIGA 2000 reactor in Bandung completed a commissioning program and received an operating license at 2000 kW. The Indonesia regulatory body (BAPETEN) issued a 15-year license, to operate the reactor at 2000 kW. During the commissioning tests, bubbling at the reactor core was observed and considered acceptable by General Atomic experts. The sub-cooled boiling observed during the commissiong tests confirmed the predictions of the thermal hydraulics calculations performed by General Atomics and presented in the safety analysis report. In 2004 the operating staff of the Bandung TRIGA 2000 Reactor observed an increase in the amount and size of the bubbles emanating from the core and in January 2005 the BAPETEN after an inspection and discussion with the operating irganization decided to limit the reactor power to 1250 kW. In January 2005, IAEA team mission organize a favt-finding mission to have a better understanding of the safety implications of the reactor bubbling and to propose an action plan to address and solve the issue. Followint this obligation, BATAN submitted to the Agency the current verison of the SAR at the end of 2007. In March 2007, IAEA team mission came to Indonesia di review the SAR was combined with the follow-up on the recommendation from previous mission on investigation of core bubbling phenomena,